Digital Literacy Practice: Pedagogical Approach with CoPORA Model on Students’ Performances in Writing Classroom - Moh. Hafidz; Pratiwi Retnaningdyah; Ali Mustofa (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study aims to describe the impact of the CoPORA model on EFL university students’ performances in accessing, communicating, integrating, evaluating, and creating information using social media in a writing classroom. Method: Data were collected using interview techniques from EFL university students and analyzed descriptively to achieve the study's objectives. Results: The CoPORA model in pedagogical digital literacy practices enables students to master English vocabulary, be motivated to communicate, develop social identity, and manage and evaluate information effectively. Key performances included creating and communicating argumentative texts with readers on social media platforms. Social media usage facilitated checking trusted sources and contents, communicating information with friends, lecturers, and followers, making cross-references among digital content and facts, proving the truth of contents, and writing and communicating argumentative texts. Novelty: The study found that pedagogical digital literacy practices using the CoPORA model positively contribute to students' mutual contributions to language learning, cognition, and social interaction in English essay-writing classrooms.